First-line treatments for advanced hepatocellular carcinoma: a network meta-analysis and cost-effectiveness analysis in China and the United States - Ke-Xin Sun; Shan-Shan Cao; Feng-Hao Shi; Yue Guan; Meng Tang; Mei-na Zhao; Yu-Fan Jian; Bin Cui; Zhi-Yan Li; Jing-Wen Wang; Feng Yu; Yi Ding (Therapeutic Advances in Gastroenterology, 2022)
Background: Various therapeutic strategies are available for the first-line treatment of patients with advanced hepatocellular carcinoma (aHCC). But which approach is the most cost-effective remains uncertain. Objectives: This study aims to evaluate the cost-effectiveness of first-line strategies in aHCC patients from the perspective of Chinese and US payers. Design: A network meta-analysis (NMA) and cost-effectiveness study. Data sources and methods: A NMA was conducted to collect all first-line strategies with aHCC from 1 October 1 2018 until 1 January 2022. The relevant randomized controlled trial literature in PubMed, Embase, and Cochrane Library for the last 3 years were searched. The abstracts of meetings of the American Society of Clinical Oncology, European Society of Medical Oncology, and American Association for Cancer Research were also reviewed. A Markov model that included three states was developed. One-way sensitivity and probabilistic sensitivity analysis were performed to investigate the uncertainty of the economic evaluation. Scenario analysis was conducted to explore the economic benefits of treatment strategies in low-income populations. Results: Base-case analysis in China included 1712 patients showed that atezolizumab combined with bevacizumab, sintilimab combined with bevacizumab, lenvatinib (LEVA), and sorafenib (SORA) added 0.46, 1.25, 0.77, and −1.08 quality-adjusted life-years (QALYs), respectively, compared with donafenib, resulting in an incremental cost-effective ratio of $85607.88, $12109.27, and $1651.47 per QALY at a willingness-to-pay (WTP) of $11101.70/QALY. In the United States, only the incremental cost-effectiveness ratios (ICERs) of SORA was higher that were lower than the WTP threshold ($69375/QALY), and LEVA was the most cost-effective strategy with the ICERs were 25022.13/QALY. Conclusion: The NMA and cost-effectiveness analysis revealed that LEVA is the favorite choice in the first-line treatment of Chinese aHCC patients and US payers’ perspective when the WTP was $11101.70/QALY in China and $69375.0/QALY in the United States. Registration: This study has been registered on the PROSPERO database with the registration number CRD42021286575.